Pedagogical Practices In Teaching Entrepreneurship Education In Universities In South-West Nigeria - Adesoji, F. A.; Sangoleye, S. A. (Advances in Social Sciences Research Journal, 2017)
The study examined the qualifications of entrepreneurship education lecturers and pedagogical practices in teaching entrepreneurship education in universities in south-west Nigeria. Stratified sampling was used to classify universities in Nigeria into federal, state and private based on ownerships of the institutions. Using simple random sampling, four universities each were selected from federal and state strata totaling eight universities while private stratum was purposively partial out. Purposive and random sampling were used to select 51 entrepreneurship education lecturers, 6 directors of EDCs and 831 400L undergraduates. Two instruments designed and validated by the investigators were used for data collection. Results indicated that non-specialists teach entrepreneusrship education; writing and presenting business plans and feasibility study is the most common teaching strategies in teaching entrepreneurship education. There is a significant influence of approach of the institution to internship on undergraduates’ disposition to self- employment (F(2,828) = 3.209; P <0.05). Hence, employment of qualified lecturers, artisans, practicing entrepreneurs and construction of incubation centres in teaching entrepreneurship education in universities in south-west Nigeria are imperative.